2015
DOI: 10.1039/c5ra12710f
|View full text |Cite
|
Sign up to set email alerts
|

A urine metabonomics study of chronic renal failure and intervention effects of total aglycone extracts of Scutellaria baicalensis in 5/6 nephrectomy rats

Abstract: This study was to clarify the pathogenesis of CRF and action mechanism of TAES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A value of P < 0.05 was considered statistically significant. For GC/MS data, data processing,significant variables selection and identification are in accordance with our previously published work (Fang et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A value of P < 0.05 was considered statistically significant. For GC/MS data, data processing,significant variables selection and identification are in accordance with our previously published work (Fang et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Urine sample preparation and sample analysis by GC/MS was performed in accordance with our previously published work (Fang et al, 2015).…”
Section: Urine Sample Preparation and Gc/ms Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…44,45 Moreover, recent research demonstrated that RS treatment regulated urinary glucose in chronic renal failure. 46 Downregulated urinary glucose level by RS treatment throughout the progress of DN implicated the potential suppressive effect of RS on SGLT1 or SGLT2. Citric acid is a major intermediate in the tricarboxylic acid (TCA) cycle.…”
Section: Changes In Energy Metabolism Pathwaymentioning
confidence: 99%